Lower fiducial limit of urinary metabolite level as an index of excessive exposure to industrial chemicals - Imamura, Toshiko (1973)
Imamura, T., and Ikeda, M. (1973).British Journal of Industrial Medicine,30, 289-292. Lower fiducial limit of urinary metabolite level as an index of excessive exposure to industrial chemicals. Utilization of the lower fiducial limit (P = 0·10), rather than the mean, as an index of excessive exposure to industrial chemicals is discussed. Cases of exposure to trichloroethylene, phenol, and toluene are used to illustrate this approach.